(untitled) (International Journal of Innovative Technologies in Economy, 2023)
The topic is relevant in that 2020 was a turning point for the labor market of the Republic of Armenia, given the consequences of the Covid-19 pandemic, and then the war. In this sense, it can be argued that a great crisis is expected in the labor market itself, since one of the characteristics of this market is that in its center there is a person offering his job. The object of the study of the article is the system of regulation of employment in the labor market of the Republic of Armenia, and the goal is to develop a new regulation model based on the results of a multifaceted analysis of the labor market of the Republic of Armenia, as well as the implementation of forecasts for changes in the number of employees by institutional sectors of the economy and types of economic activity for 2023-2030. To achieve the goal, the following tasks were proposed and solved: • The dynamics of the number of employed in different sectors of the economy was analyzed: industry, energy, construction, trade and services. • A correlation model was developed, the results of the correlation analysis were evaluated and presented. • The forecasts of changes in the number of employees by institutional sectors of the economy and types of economic activity for 2023-2030 have been made.